Sources, Effects and Risks of Ionizing Radiation, United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) 2013 Report, Volume II - United Nations Scientific Committee on the Effects of Atomic Radiation (United Nations, 2014)
The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) assesses the levels and effects of exposure to ionizing radiation. UNSCEAR’s scientific findings underpin radiation risk evaluation and international protection standards. This is the second of two parts of scientific annexes that provide the supporting scientific assessment for UNSCEAR’s 2013 report to the General Assembly. This scientific annex on “effects of radiation exposure of children” provides a detailed review of scientific material that deals with special aspects of radiation dosimetry in children, cancer incidence after radiation exposure in childhood and the direct effects that occur after high doses (deterministic health effects). It examines the differences between the effects occurring after radiation exposure in childhood and those in adulthood.